2015
DOI: 10.14740/jocmr2108w
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Maternal-Fetal Outcomes After Emergency Vaginal Cerclage Performed With Shirodkar-McDonald Combined Modified Technique

Abstract: BackgroundSeveral techniques of emergency vaginal cerclage have been proposed in case of unexpected and abrupt cervical incompetence (CI), in order to prolong the pregnancy as much as possible and to reduce the adverse maternal-fetal outcomes. The aim of our study was to evaluate the effectiveness of emergency cervical cerclage, performed with the combined modified Shirodkar-McDonald technique.MethodsWe selected 12 cases of emergency vaginal cerclage, performed between January 1, 2008 and June 30, 2013. The ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
(21 reference statements)
2
5
0
Order By: Relevance
“…Positive results of the emergency suture application were also confirmed in a study of Ciancimino et al [ 69 ]. A total of 12 patients underwent emergency suture placement.…”
Section: Rescue Suture Effectivenesssupporting
confidence: 59%
See 1 more Smart Citation
“…Positive results of the emergency suture application were also confirmed in a study of Ciancimino et al [ 69 ]. A total of 12 patients underwent emergency suture placement.…”
Section: Rescue Suture Effectivenesssupporting
confidence: 59%
“…A total of 12 patients underwent emergency suture placement. Pregnancy was extended by an average of 89.9 days, and neonatal survival was 83.3% [ 69 ]. Equally good results were obtained by Cavus et al [ 70 ], who analyzed pregnancy outcomes in 20 patients who experienced cervical cerclage in the second trimester with an average of 4.3 cm cervical dilation.…”
Section: Rescue Suture Effectivenessmentioning
confidence: 99%
“…This study is similar to the study of Stupin et al (2008). In the series of Ciancimino et al (2015), a total of 12 patients underwent emergency suture placement. Pregnancy was extended upto 89.9 days and neonatal survival was 83.3%.…”
Section: Resultssupporting
confidence: 68%
“…[15][16][17][18][19][20] Currently, two of the most commonly performed cerclage procedures are modifications of Shirodkar and McDonald. 21,22 ECC may have a higher chance of failure, and other complications such as preterm premature rupture of membranes (PPROM) and chorioamnionitis are more common. 23,24 It has been suggested that cerclage placement closer to the internal os may be associated with improved perinatal outcome.…”
Section: Introductionmentioning
confidence: 99%